Inactivation of Gi proteins by pertussis toxin diminishes the effectiveness of adrenergic stimuli in conduit arteries from spontaneously hypertensive rats - Zemančíková, Anna; Török, Jozef; Zicha, Josef; Kuneš, Jaroslav (Physiological research, 2008)
Treatment with pertussis toxin (PTX) which eliminates the activity of G(i) proteins effectively reduces blood pressure (BP) and vascular resistance in spontaneously hypertensive rats (SHR). In this study we have compared the functional characteristics of isolated arteries from SHR with and without PTX-treatment (10 microg/kg i.v., 48 h before the experiment). Rings of thoracic aorta, superior mesenteric artery and main pulmonary artery were studied under isometric conditions to measure the reactivity of these vessels to receptor agonists and to transmural electrical stimuli. We have found that the treatment of SHR with PTX had no effect on endothelium-dependent relaxation of thoracic aorta induced by acetylcholine. In PTX-treated SHR, the maximum contraction of mesenteric artery to exogenous noradrenaline was reduced and the dose-response curve to cumulative concentration of noradrenaline was shifted to the right. Similarly, a reduction in the magnitude of neurogenic contractions elicited by electrical stimulation of perivascular nerves was observed in the mesenteric artery from PTX-treated SHR. PTX treatment of SHR also abolished the potentiating effect of angiotensin II on neurogenic contractions of the main pulmonary artery. These results indicate that PTX treatment markedly diminishes the effectiveness of adrenergic stimuli in vasculature of SHR. This could importantly affect BP regulation in genetic hypertension.
Keywords: GTP-Binding Protein alpha Subunits, Gi-Go; Animals; elektrická stimulace; Electric Stimulation; Rats; hypertenze; angiotensin II; Aorta, Thoracic; Endothelium, Vascular; arteria pulmonalis; acetylcholin; Enzyme Inhibitors; Adrenergic Agents; noradrenalin; Pulmonary Artery; proteiny vázající GTP - alfa-podjednotky Gi-Go; signální transdukce; Rats, Inbred SHR; Signal Transduction; krevní tlak; Arteries; Hypertension; Male; Acetylcholine; inhibitory enzymů; aorta thoracica; Pertussis Toxin; krysa rodu Rattus; cévní endotel; potkani inbrední SHR; arteria mesenterica superior; pertusový toxin; zvířata; mužské pohlaví; Blood Pressure; Mesenteric Artery, Superior; adrenergní látky; arterie; Norepinephrine; Angiotensin II